STUDIES ON THE IMPACT OF THE PARAVANAR RIVER POLLUTANTS ON GLUCOSE AND GLYCOGEN LEVEL OF FRESHWATER PRAWN, MACROBRACHIUM MALCOLMSONII (H. MILNE EDWARDS) - M. MANOSATHIYADEVAN; SELVISABHANAYAKAM (The Bioscan, 2011)
In the present study, to find out the impact of Paravanar river pollutants on freshwater prawn, Macrobrachium malcolmsonii collected from three Stations viz., Station-I, Station-II and Station-III such as, Unpolluted (StationI), Less polluted (Station-II) and More polluted (Station-III) regions. Biochemical changes such as glucose and glycogen contents were analyzed in various organs like, gills, testis, vasdeferens, hepatopancreas, and androgenic gland. A decline in glycogen content and an increase in glucose content in all the tissues of freshwater prawn, Macrobrachium malcolmsonii collected from three stations were secured. There was a significant difference (p<0.01) in the quantitative biochemical parameters such as glucose and glycogen content. The results obtained are discussed in details.